2020
DOI: 10.3390/cancers12102919
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly Expressed RECQL4 Helicase Supports Proliferation and Drug Resistance of Human Glioma Cells and Glioma Stem Cells

Abstract: Anti-tumour therapies eliminate proliferating tumour cells by induction of DNA damage, but genomic aberrations or transcriptional deregulation may limit responses to therapy. Glioblastoma (GBM) is a malignant brain tumour, which recurs inevitably due to chemo- and radio-resistance. Human RecQ helicases participate in DNA repair, responses to DNA damage and replication stress. We explored if a helicase RECQL4 contributes to gliomagenesis and responses to chemotherapy. We found upregulated RECQL4 expression in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Our earlier study suggested the possibility that RecQL4 can potentially regulate the expression of genes such as MDR1 and YB1 in gastric cancer cells. In support, Król et al [2020] demonstrated that RecQL4 silencing in LN18 cells caused transcriptomic changes with 3,056 downregulated genes and 1,699 upregulated genes. Some of the downregulated genes belong to the pathways of ribosome biogenesis, RNA transport, RNA degradation, and protein synthesis in endoplasmic reticulum.…”
Section: Recql4 Protects Cancer Cells From Endogenous and Exogenous Dna Damagementioning
confidence: 88%
See 3 more Smart Citations
“…Our earlier study suggested the possibility that RecQL4 can potentially regulate the expression of genes such as MDR1 and YB1 in gastric cancer cells. In support, Król et al [2020] demonstrated that RecQL4 silencing in LN18 cells caused transcriptomic changes with 3,056 downregulated genes and 1,699 upregulated genes. Some of the downregulated genes belong to the pathways of ribosome biogenesis, RNA transport, RNA degradation, and protein synthesis in endoplasmic reticulum.…”
Section: Recql4 Protects Cancer Cells From Endogenous and Exogenous Dna Damagementioning
confidence: 88%
“…Data from Tumor Cell Genome Atlas (TCGA) show an association between RecQL4 expression and some of the stem cell markers such as Nestin, Musashi-1, Myc, and CD133. Further, RecQL4 expression was found to be higher in LN18 cells grown as spheres than adherent cell monolayers [Król et al, 2020]. This observation is particularly relevant because glioblastoma cells are usually rich in cancer stem cells that can cause tumor recurrence.…”
Section: Recql4 Protects Cancer Cells From Endogenous and Exogenous Dna Damagementioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, CSCs exhibit mesenchymal stem cell (MSC) phenotype [ 21 ], and their presence was reported in many sarcoma subtypes, including rhabdomyosarcoma, synovial sarcoma, undifferentiated pleomorphic sarcoma, and osteosarcoma [ 22 , 23 ]. Nowadays, SSCs are considered essential drivers of disease progression and relapse [ 24 ] and are therefore important targets for novel oncological therapies [ 25 , 26 ].…”
Section: Chondrosarcoma Stem Cellmentioning
confidence: 99%